2009
DOI: 10.1097/meg.0b013e32830e28b2
|View full text |Cite
|
Sign up to set email alerts
|

Increased number of methylated CpG islands correlates with Helicobacter pylori infection, histological and serological severity of chronic gastritis

Abstract: Multiple promoter CpG islands would be methylated by H. pylori infection, and an increased number of methylated CpG sites correlate with histological and serological severity of chronic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
84
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(100 citation statements)
references
References 16 publications
13
84
3
Order By: Relevance
“…All the subjects underwent upper gastroscopy as part of a health check, as a secondary procedure following barium X-ray examination for suspected stomach cancer, or for the investigation of abdominal discomfort. This cohort was partly recruited from recent study investigating the association between promoter CIHM and severity of chronic gastritis (12), host genetic factors (31). Patients who had severe systemic disease, or malignancy in the stomach or other organ, who had a history of gastric surgery were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All the subjects underwent upper gastroscopy as part of a health check, as a secondary procedure following barium X-ray examination for suspected stomach cancer, or for the investigation of abdominal discomfort. This cohort was partly recruited from recent study investigating the association between promoter CIHM and severity of chronic gastritis (12), host genetic factors (31). Patients who had severe systemic disease, or malignancy in the stomach or other organ, who had a history of gastric surgery were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Methylation of DAP-kinase has been reported in many cancers (8) including gastric cancer (9,10). It has also been reported that CIHM of those 4 genes are frequently occurred in non-cancerous gastric mucosa in relation to H. pylori infection (7,11,12), histological or serological severity of gastritis (12) and gastric cancer occurrence (13)(14)(15). Therefore, they may be susceptible candidate genes for CIHM in the stomach.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rates of hypermethylation were variable, ranging from 30% to 82%. 8,19 In addition, some studies reported that methylation of MLH1 and MGMT did not decrease significantly after H. pylori eradication. 8,20 Conversely, a recent study showed that MGMT methylation was significantly reduced after H. pylori eradication in patients with H. pylori gastritis (from 70% to 48%).…”
Section: Discussionmentioning
confidence: 99%